2021
DOI: 10.1155/2021/8880141
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Cyanidin‐3‐Glucoside on Myocardial Ischemia‐Reperfusion Injury through Ferroptosis

Abstract: This study was conducted to estimate the protective effect of Cyanidin-3-glucoside (C3G) on myocardial ischemia-reperfusion (IR) injury and to explore its mechanism. The rats were subjected to left anterior descending ligation and perfusion surgery. In vitro experiments were performed on H9c2 cells using the oxygen-glucose deprivation/reoxygenation (OGD/R) model. The results showed the administration of C3G reduced the infarction area, mitigated pathological alterations, inhibited ST segment elevation, and att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 32 publications
1
50
0
Order By: Relevance
“…In experimental models, inhibition of glutaminolysis, an important part of ferroptosis, was shown to reduce I/R-induced heart injury [ 70 ]. Studies have confirmed that ROS accumulation and iron content increase during I/R injury [ 71 , 72 ], and iron overload is an important cause of myocardial cell injury [ 73 ]. A study by Li et al showed that iron deposition and ROS overproduction occurred during diabetic myocardial injury, and ferroptosis was involved in the I/R injury of diabetic myocardium through the endoplasmic reticulum stress pathway [ 31 ].…”
Section: Pathological Mechanisms and Potential Targeted Therapy Of Ferroptosis In Ischemia-reperfusion Injurymentioning
confidence: 99%
“…In experimental models, inhibition of glutaminolysis, an important part of ferroptosis, was shown to reduce I/R-induced heart injury [ 70 ]. Studies have confirmed that ROS accumulation and iron content increase during I/R injury [ 71 , 72 ], and iron overload is an important cause of myocardial cell injury [ 73 ]. A study by Li et al showed that iron deposition and ROS overproduction occurred during diabetic myocardial injury, and ferroptosis was involved in the I/R injury of diabetic myocardium through the endoplasmic reticulum stress pathway [ 31 ].…”
Section: Pathological Mechanisms and Potential Targeted Therapy Of Ferroptosis In Ischemia-reperfusion Injurymentioning
confidence: 99%
“…Cyanidin-3-glucoside (C3G) treatment can effectively alleviate the expression of proteins related to apoptosis, reduce Fe 2+ content, and improve MIRI. Therefore, C3G is a potential medicine to prevent myocardial cells from being affected by MIRI [ 85 ].…”
Section: The Role Of Ferroptosis In Mirimentioning
confidence: 99%
“…Lv et al (2021) proved that Etomidate suppressed ferroptosis in IRI model via upregulation of Nrf2 and heme oxygenase-1 (HO-1) protein expression. Cyanidin-3-glucoside, a kind of anthocyanin, is verified to attenuate myocardial IRI via ferroptosis inhibition by reducing oxidative stress and Fe 2+ accumulation in vivo and in vitro ( Shan et al, 2021 ). Ma et al (2020) demonstrated that USP22 (ubiquitin-specific protease 22), a member of the deubiquitinase family, could inhibit ferroptosis in myocardial IRI via the SIRT1/p53/SLC7A11 association.…”
Section: Ferroptosis and Cvdsmentioning
confidence: 99%